A Systematic Review of Intrinsic and Extrinsic Motivation in EFL Classrooms: Implications for Student Engagement and Learning Outcomes - Anjas Moro; Alda Fuadiyah; Sifa Irvana Zain; Anisa Fitrianida (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
Motivation is a crucial factor influencing students’ engagement and achievement in English as a Foreign Language (EFL) learning. This study aims to systematically review recent research on intrinsic and extrinsic motivation in EFL classrooms and to examine their implications for student engagement and learning outcomes. Employing a qualitative systematic literature review design, 20 peer-reviewed articles published between 2020 and 2025 were selected through a PRISMA-based screening process and analyzed using thematic synthesis. The findings indicate that intrinsic motivation, driven by enjoyment, autonomy, and personal relevance, is strongly associated with sustained cognitive, emotional, and behavioral engagement as well as long-term language development, whereas extrinsic motivation, shaped by grades, examinations, institutional demands, and future career expectations, effectively supports short-term academic performance and task completion but is less strongly related to lasting communicative competence. The review further reveals that motivational orientations are highly context-dependent, particularly in exam-oriented and digitally mediated learning environments. This study proposes a conceptual perspective termed motivational magnetism, referring to the dynamic interaction between autonomy-supportive instruction and performance-oriented demands in sustaining learners’ engagement, and suggests that EFL teachers should balance intrinsic and extrinsic motivational strategies to enhance both academic achievement and long-term learner engagement.ABSTRAKMotivasi merupakan faktor krusial yang memengaruhi keterlibatan dan prestasi siswa dalam pembelajaran Bahasa Inggris sebagai Bahasa Asing (EFL). Penelitian ini bertujuan untuk melakukan tinjauan sistematis terhadap penelitian terkini mengenai motivasi intrinsik dan ekstrinsik di kelas EFL, serta menganalisis implikasinya terhadap keterlibatan siswa dan hasil belajar. Menggunakan desain tinjauan literatur sistematis kualitatif, 20 artikel yang telah direview oleh rekan sejawat yang diterbitkan antara tahun 2020 dan 2025 dipilih melalui proses penyaringan berdasarkan PRISMA dan dianalisis menggunakan sintesis tematik. Temuan menunjukkan bahwa motivasi intrinsik, yang didorong oleh kesenangan, otonomi, dan relevansi pribadi, memiliki hubungan yang kuat dengan keterlibatan kognitif, emosional, dan perilaku yang berkelanjutan serta perkembangan bahasa jangka panjang. Di sisi lain, motivasi ekstrinsik, yang dipengaruhi oleh nilai, ujian, tuntutan institusional, dan harapan karir masa depan, secara efektif mendukung kinerja akademik jangka pendek dan penyelesaian tugas, tetapi kurang terkait erat dengan kompetensi komunikatif yang berkelanjutan. Tinjauan ini juga mengungkapkan bahwa orientasi motivasi sangat bergantung pada konteks, terutama dalam lingkungan pembelajaran yang berorientasi ujian dan didukung teknologi digital. Studi ini mengusulkan perspektif konseptual yang disebut “magnetisme motivasi,” merujuk pada interaksi dinamis antara instruksi yang mendukung otonomi dan tuntutan berorientasi kinerja dalam mempertahankan keterlibatan peserta didik, dan menyarankan agar guru bahasa Inggris sebagai bahasa asing (EFL) menyeimbangkan strategi motivasi intrinsik dan ekstrinsik.